THE EFFECT OF THIRD PARTY FUNDS, CAPITAL ADEQUACY, AND CREDIT RISK ON BANKING PERFORMANCE IN INDONESIA - Yenni Vera Fibriyanti; Akhlis Priya Pambudy (Jurnal Scientia, 2023)
This study aims to analyze the effect of third party funds, capital adequacy ratios and credit risk on the financial performance of banks in Indonesia. The data used in this research is secondary data. Meanwhile, the samples in this study were banking companies listed on the IDX during the 2018-2022 period. The method used is porposive sampling and there are 24 banks that are included in the criteria of this study. The results showed that third party funds (X1) had a positive and significant effect on financial performance because the value of tcount > ttable was 8.294 > 1.97993. The capital adequacy variable (X2) has no partial effect on financial performance (ROA) because the tcount < ttable is 1.405 < 1.97993. The credit risk variable (X3) has a negative and significant effect on financial performance (ROA) because the tcount < ttable is -3.834 < 1.97993. Third Party Funds, Capital Adequacy and Credit Risk simultaneously affect the financial performance of banks listed on the IDX in 2018 – 2022. This can be seen from the significance level of the F test which produces a value of Fcount > Ftable, namely 26.082 > 2.68.